Foundations of earth science - Lutgens, Frederick K. (Pearson, 2014)
"Foundations of earth science, 7th edition, is a college-level text designed for an introductory course in earth science. It consists of seven units that emphasize broad and up-to-date coverage of basic topics and principles in geology, oceanography, meteorology, and astronomy. The book is intended to be a meaningful, nontechnical survey for undergraduate students with little background in science. Usually these students are taking an earth science class to meet a portion of their college or university's general requirements"-- Provided by publisher.